Marketing Communication Strategy at Fashion Company "X" During a Pandemic Covid-19 - Jerry Indrawan; Felicia Goenawan; Ido Prijana Hadi (Journal of Content and Engagement, 2023)
This research was conducted to find out how the marketing communication strategy was carried out by fashion company "X" during the Covid-19 pandemic. In its marketing communication strategy, fashion company "X" has the goal of increasing sales of the products sold by fashion company "X". In achieving this goal, the fashion company "X" uses the AIDA model (Action, Interest, Desire, Action) to classify a person's phases in knowing a brand and taking action and using the elements in integrated marketing communication (IMC) to analyze strategy marketing communications used by fashion company "X". This type of research is descriptive qualitative. And using the case study method as well as in collecting data using interview techniques. In delivering its marketing communication strategy, fashion company "X" uses several online media according to their target market. In addition, they also use live shopping techniques. and the latter uses the data of every customer who purchases at their company to offer the latest products from fashion company "X". The results of this study are used to determine marketing communication strategies at the fashion company "X" during the Covid-19 pandemic and the latter uses the data of every customer who purchases at their company to offer the latest products from fashion company "X". The results of this study are used to determine marketing communication strategies at the fashion company "X" during the Covid-19 pandemic and the latter uses the data of every customer who purchases at their company to offer the latest products from fashion company "X". The results of this study are used to determine marketing communication strategies at the fashion company "X" during the Covid-19 pandemic